Jean-Yves Lacoste’s phenomenology of liturgy as philosophy of mysticism - ZGÓRECKI, PRZEMYSŁAW (Filozofia Chrześcijańska, 2021)
Phenomenology of liturgy is the main philosophical project of Jean-Yves Lacoste, a contemporary French thinker, up to this time not well known in Poland. Liturgy is hereby understood in a broader sense, as a mode of life, which consist of facing God, understood as a subject and a promise of relationship. Therefore, it seems to be both a philosophical and mystical experience, which is why it is going to be considered here as philosophy of mysticism. The paper examines Lacoste’s undertaking of the task of thinking, his way to philosophy of mysticism, as well as the relation between philosophical and mystical experience in his thought. Finally, a question will emerge: is mysticism in its core a way of experiencing time?